Adaptive Stress Coping in Awake Bruxism - Soto-Goñi, Xabier Ander; Alen, Francisco; Buiza-González, Leticia; Marcolino-Cruz, Danielle; Sánchez-Sánchez, Teresa; Ardizone-García, Ignacio; Aneiros-López, Fernando; Jiménez-Ortega, Laura (Frontiers in Neurology, 2020)
Numerous studies have analyzed the relationship between psychological factors and bruxism. However, the data are often obscured by the lack of precise diagnostic criteria and the variety of the psychological questionnaires used. The purpose of this study is to determine the association between awake bruxism and psychological factors (anxiety, depression, sociability, stress coping and personality traits). With this aim, 68 participants (13 males) completed a battery of psychological questionnaires, a self-reported bruxism questionnaire, and a clinical examination. Based on their scores on the bruxism questionnaire and the clinical examination, subjects were divided into two groups. Subjects who met the criteria for “probable awake bruxism” were assigned to the case group (n = 29, 5 males). The control group (n = 39, 9 males) was composed of subjects who showed no signs or symptoms of bruxism in the examination nor in the questionnaire. The probable awake bruxism group presented significantly higher levels of trait and state anxiety, symptoms of somatization, and neuroticism than the control group. Despite this, and when their problem coping strategies were considered, awake bruxers showed higher levels in Positive Reappraisal (p< .05), a strategy generally considered as adaptive. In conclusion, although awake bruxers in our study showed larger levels of anxiety, somatization, and neuroticism, they also displayed more adapted coping strategies, while according to previous data TMD patients (which generally also present high levels of anxiety, somatization and neuroticism) might tend to present less adaptive coping styles. Thus, awake bruxism may play a positive role in stress coping, which would be compatible with the hypothesis of mastication as a means of relieving psychological tension. This finding should be further confirmed by future research comparing TMD patients with definitive awake bruxers and controls and using larger and more representative samples.